2010
DOI: 10.2108/zsj.27.917
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of Sexual Size Dimorphism in Monitor Lizards: Males Grow for a Longer Period, but not at a Faster Rate

Abstract: Monitor lizards belong to the largest and the most sexually dimorphic lizards in terms of size, making this group an ideal model for studies analyzing ontogenetic causes of sexual dimorphism. Understanding of these ontogenetic factors is essential to the current discussion concerning patterns of sexual dimorphism in animals. We examined the ontogenetic trajectories of body weight and snout-vent length to analyze the emergence of sexual size dimorphism. Experimental animals were 22 males and 13 females of mangr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 47 publications
1
15
0
1
Order By: Relevance
“…We applied a three-parameter logistic regression model (Equation 1 ) to analyse the growth trajectories of the overall sample of a given species, hybrids, backcrosses. We have previously found that this model 22 fits very well the data covering the body growth of reptiles from hatching to adulthood 9 . We used the Levenberg-Marquardt algorithm (with 1000 maximum number of iterations), which minimized the sum of squares between the predicted and observed growth values.…”
Section: Methodssupporting
confidence: 54%
“…We applied a three-parameter logistic regression model (Equation 1 ) to analyse the growth trajectories of the overall sample of a given species, hybrids, backcrosses. We have previously found that this model 22 fits very well the data covering the body growth of reptiles from hatching to adulthood 9 . We used the Levenberg-Marquardt algorithm (with 1000 maximum number of iterations), which minimized the sum of squares between the predicted and observed growth values.…”
Section: Methodssupporting
confidence: 54%
“…Similar to most other vertebrates (Badyaev, 2002), male and female squamates are nearly identical in size at birth/hatching, with SSD being developed only later in ontogeny (Kratochvíl and Frynta, 2002;Taylor and DeNardo, 2005;Frynta et al, 2010;Starostová et al, 2010;Bonnet et al, 2011;Kubicǩa et al, 2013). But what is the nature of the sex-specific growth regulators and modifiers that lead to the ontogeny of SSD?…”
Section: Introductionmentioning
confidence: 96%
“…In the present paper, we paid attention to morphological characteristics (size) and counts of blood cells of monitor lizards (i.e. the group exhibiting extreme changes in body size from both phylogenetic and ontogenetic perspectives) (see Pianka 1995;Frynta et al 2010). In contrast to the above studies relying on between-species comparisons, we focused on the within-species relationships between blood cell size and body size assessed during the course of ontogeny.…”
Section: Introductionmentioning
confidence: 99%
“…The mangrove-dwelling monitor (Varanus indicus Daudin, 1802) belongs to the subgenus Euprepriosaurus inhabiting New Guinea and surrounding areas (see Ast 2001;Böhme 2003). V. indicus is a representative of a closely related group of medium-to-large bodied species (Ziegler et al 2007;Koch et al 2009) exhibiting apparent sexual size dimorphism in adult body size Frynta et al 2010;Frýdlová et al 2011). These animals can live approximately 17 years and reach sexual maturity at 1.5 years old ).…”
Section: Introductionmentioning
confidence: 99%